Delineation and Modulation of the Natural Killer Cell Transcriptome in Rhesus Macaques During ZIKV and SIV Infections - Aid, Malika; Ram, Daniel R.; Bosinger, Steven E.; Barouch, Dan H.; Reeves, R. Keith (Frontiers in Cellular and Infection Microbiology, 2020)
Natural killer (NK) cells are crucial regulators of antiviral and anti-tumor immune responses. Although in humans some NK cell transcriptional programs are relatively well-established, NK cell transcriptional networks in non-human primates (NHP) remain poorly delineated. Here we performed RNA-Seq experiments using purified NK cells from experimentally naïve rhesus macaques, providing the first transcriptional characterization of pure NK cells in any NHP species. This novel NK cell transcriptomic signature (NK RMtsig) overlaps with published human NK signatures, allowing us to identify new key signaling and transcription factor networks underlying NK cell function. Finally, we show that applying NK RMtsig to an unrelated rhesus macaque cohort infected with SIVmac251 or ZIKV can sensitively detect NK cell repertoire perturbations, thus confirming applicability of this approach. In sum, we propose this NHP NK cell signature will serve as a useful resource for future studies involving infection, disease or treatment modalities in NHP.